IL-33 promotes food anaphylaxis in epicutaneously sensitized mice by targeting mast cells - Galand, Claire; Leyva-Castillo, Juan Manuel; Yoon, Juhan; Han, Alex; Lee, Margaret S.; McKenzie, Andrew N.J.; Stassen, Michael; Oyoshi, Michiko K.; Finkelman, Fred D.; Geha, Raif S. (Journal of allergy and clinical immunology, 2016)
Cutaneous exposure to food allergens predisposes to food allergy, which is commonly associated with atopic dermatitis (AD). Levels of the epithelial cytokine IL-33 are increased in skin lesions and serum of patients with AD. Mast cells (MCs) play a critical role in food-induced anaphylaxis and express the IL-33 receptor ST2. The role of IL-33 in patients with MC-dependent food anaphylaxis is unknown. We sought to determine the role and mechanism of action of IL-33 in patients with food-induced anaphylaxis in a model of IgE-dependent food anaphylaxis elicited by oral challenge of epicutaneously sensitized mice. Wild-type, ST2-deficient, and MC-deficient KitW-sh/W-sh mice were epicutaneously sensitized with ovalbumin (OVA) and then challenged orally with OVA. Body temperature was measured by means of telemetry, Il33 mRNA by means of quantitative PCR, and IL-33, OVA-specific IgE, and mouse mast cell protease 1 by means of ELISA. Bone marrow–derived mast cell (BMMC) degranulation was assessed by using flow cytometry. Il33 mRNA expression was upregulated in tape-stripped mouse skin and scratched human skin. Tape stripping caused local and systemic IL-33 release in mice. ST2 deficiency, as well as ST2 blockade before oral challenge, significantly reduced the severity of oral anaphylaxis without affecting the systemic TH2 response to the allergen. Oral anaphylaxis was abrogated in KitW-sh/W-sh mice and restored by means of reconstitution with wild-type but not ST2-deficient BMMCs. IL-33 significantly enhanced IgE-mediated degranulation of BMMCs in vitro. IL-33 is released after mechanical skin injury, enhances IgE-mediated MC degranulation, and promotes oral anaphylaxis after epicutaneous sensitization by targeting MCs. IL-33 neutralization might be useful in treating food-induced anaphylaxis in patients with AD. [Display omitted]